Salvia sclarea L. (Clary Sage) flower extract-mediated green synthesis of silver nanoparticles and their characterization, antibacterial, antifungal, and scolicidal activities against Echinococcus granulosus - Zahra Zarei; Damoun Razmjoue; Mohammad Moazeni; Hossein Azarnivand; Fatemeh Oroojalian (The Microbe)
Over the past few decades, nanoscience has gained a prominent position in plant-mediated synthesis of nanoparticles due to its advantages, such as environment-friendly and practical nature and biological safety and compatibility. This study was conducted to develop silver nanoparticles (NPs) based on Salvia sclarea flower extract and characterize them using UV–visible spectroscopy, Dynamic Light Scattering, Zeta potential analysis, Fourier Transform Infrared Spectroscopy, X-ray diffraction, Field Emission Scanning Electron Microscopy, and Transmission electron microscopy. We also evaluated the antibacterial (4 standard bacterial strains), anti-Candida (40 clinical isolates), and scolicidal activities of the green-synthesized Ag NPs. The characteristic absorption peak at 440 nm indicated the successful synthesis of AgNPs with spherical morphology and a size range of 30–40 nm according to TEM imaging. The FT-IR spectrum revealed the presence of functional constituents such as phenols, terpenoids, and saponins in the flower extract that could reduce metal ions and form AgNPs. EDX analysis confirmed the presence of silver (91.3 %) in the synthesized NPs. In addition, AgNPs exhibited remarkable antimicrobial activity. The highest antibacterial and antifungal activities of AgNPs were observed against Bacillus cereus and Candida krusei, respectively, while the lowest activities were observed against Pseudomonas aeruginosa and Candida albicans. At the concentration of 320 μg/mL, AgNPs delivered the highest percentage of mortality (100 %) against liver hydatid cyst protoscoleces within 15 minutes. Our findings highlight the potential of S. sclarea extract as an inexpensive and readily available material for producing biogenic AgNPs with versatile applications.